Integrating Artificial Intelligence and Digital Marketing To Enhance Msme Competitiveness in Geotourism: A Participatory Training Model in The Pangandaran Geopark - Ayu Krishna Yuliawati; Rofi Rofaida; Budhi Gautama Pamungkas; Irene Christiany; Danish Febrianto Putra; Asti Nur Aryanti; Mohamad Sapari Dwi Hadian (International Journal Of Community Service, 2026)
This community service program aims to enhance the competitiveness of micro, small, and medium enterprises (MSMEs) engaged in geotourism within the Aspiring Pangandaran Geopark through the integration of Artificial Intelligence (AI) and digital marketing using a participatory training model. MSMEs in the region face challenges such as limited digital innovation, inadequate technological access, and low capability in social media-based promotion. To address these issues, the program applied a participatory approach and speculative design thinking involving MSME owners, academics, and tourism destination managers in collaborative learning. The training consisted of three main modules: (1) digital literacy and cybersecurity for entrepreneurs, (2) the use of AI in digital marketing strategies (AI-driven storytelling, content generation, and consumer analytics), and (3) creative promotional artifact development based on local geodiversity and biodiversity. The results indicate significant improvements in participants’ ability to create digital content, understand online market opportunities, and utilize basic AI tools (chatbots, image generators, and social media analytics) to expand promotional reach. The participatory training model demonstrated positive social impacts, including strengthened MSME community networks, increased visibility of geopark-based products, and contributions to sustainable local economic development. The findings confirm that integrating AI and digital literacy represents an innovative strategy for community-based MSME empowerment in geopark areas.